Survey of Interest in Cycling During the Covid-19 Pandemic - Ishak Bachtiar; M. Imran Hasanuddin (JUARA : Jurnal Olahraga, 2022)
This research is motivated by the fact that interest in cycling has increased during the current pandemic. Many communities routinely cycle, one of which is the Makassar Folding Bike (SLIM) community. The problem in this research is the interest in cycling during the pandemic of the Makassar folding bike community in terms of the factors and elements of interest. His study aimed to discover good in cycling during the pandemic in the Makassar folding bike community in terms of the characteristics and aspects of interest. This research method is survey research. The population in this study were all members of the Makassar folding bike community, totalling 263 people. At the same time, the number of samples in this study amounted to 26 people. The sampling technique in this study was random sampling technique or random selection. The variable used is the interest in cycling during the pandemic in the Makassar Folding Bike community. The results of this study indicate that in this study, it was found that Interest in Cycling During the Covid-19 Pandemic in the Folding Bike Community was in the moderate interest category (42%).